Evaluation of a simulation-based clinical preparation program by final-year medical students: A qualitative study on emergency patient management - GÜLPINAR, MEHMET ALİ (My University, 2021)
Background: The most common problem encountered by medical students is the management of unstable emergency patients. Simulation-based education (SBE) is widely used for improving the management of unstable patients. In this study, the aim is to evaluate the SBE Clinical Preparation Program and to understand whether our final-year medical students could transfer the skills acquired in the program to clinical encounters in their emergency medicine clerkship, with the aim of easing this transition. Materials and methods: Final-year medical students at the Acıbadem Mehmet Ali Aydınlar University Faculty of Medicine and their educators were included in this qualitative study. After participating in the SBE Clinical Preparation Program for two weeks, interns completed a two-month emergency medicine clerkship. At the end of the clerkship, four focus group discussions with 5 or 7 interns (n=24) and in-depth interviews with two educators were held. The digital audio recordings were transcribed verbatim within 48 hours of the interviews. The texts were reviewed by two different researchers, and thematic codes were identified. Results: In this study, the effectiveness of the SBE Clinical Preparation Program was evaluated. The participants stated that the program prepared them very well for critical patient management and that the content of the program was sufficient and comprehensive. The trainers stated that the simulation program prepared the students well for the clinic and provided a strong foundation, which was very important, but the students had to overcome an emotional barrier when approaching real patients, a process that took one or two weeks. The characteristics of the students (motivation, anxiety levels), the quality of the processes experienced during the program (seeing a sufficient number of patients, communication and interaction with other healthcare professionals and patients) and the environment/context in which these practices took place (learning climate) were the important factors influencing the transfer of the learning outcomes to the clinical environment. Conclusion SBE transition programs are effective in preparing students for the management of critical patients and facilitate the transition to the clerkship. SBE programs are not sufficient by themselves and should be developed in a continuous and integrated manner with training programs in actual clinical settings